Rasio Keuangan dan Pengaruhnya Terhadap Profitabilitas Pada Bank Pembiayaan Rakyat Syariah - Syawal Harianto (Faculty of Economic and Business, 2017)
Financial Ratio and It's Impact on Profitability in The Indonesian Islamic Rural BanksIslamic rural banks same like as usual Islamic commercial banks that profit oriented. The aim of this research is to examine the factors that influenc the profitability in Islamic rural banks. The methods that used in this research is multiple regression. The result shows that only efficiency operational ratio (BOPO) and non-performing finance (NPF) that had impact on profitability. The profitability measured by return on asset (ROA). Otherwise, financing to deposit ratio (FDR) and capital adequacy ratio (CAR) doesn’t had an impact on Islamic rural bank’s profitability. This research implies that Islamic rural banks should increase the operational efficiency and reduce the non-performing finance.DOI: 10.15408/ess.v7i1.4076